Anesthetic use of eugenol and benzocaine in juveniles of red tilapia (Oreochromis sp.) - Rucinque, Daniel Santiago; Polo, Gina; Borbón, Javier; González Mantilla, Jaime F. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: routine practices such as biometrics, transportation and medical procedures are a source of stress to fish. The use of anesthetics is recommended to reduce undesirable effects of stress, such as decreased feed intake and even mortality -in critical cases. Objective: the aim of this study was to determine the anesthetic efficacy of eugenol and benzocaine in juveniles of red tilapia Oreochromis sp. Methods: thirty juveniles of red tilapia (Oreochromis sp.) were distributed in groups of 10 individuals as follows; G1: eugenol (50 mg/L), G2: eugenol (100 mg/L) and G3: benzocaine (100 mg/L). The fish were individually placed in the corresponding anesthetic solution. After immersion, times to achieve the different anesthetic stages were recorded. During anesthesia, the fish were measured, weighed and blood samples were collected for glucose and plasma cortisol analysis. Results: time to total loss of equilibrium was higher in G3 (p<0.05) compared to the other two groups. No significant differences were observed among groups regarding time to total loss of equilibrium or time to ventilation absence. Glucose levels were significantly higher in G1 (p = 0.03) in comparison to G3. However, cortisol levels were higher in G3 as compared to the other groups (p<0.05). A mortality rate of 10% was observed in G1 fish. Conclusion: current findings indicate that 100 mg/L eugenol leads to induction of anesthesia in less than 3 min and recovery in less than 5 min, without mortality in juveniles of red tilapia.